Dynamic Unemployment along Recessions and Recoveries: The U.S. Experience 1968 – 2015 - Annala, Christopher; Gu, Anthony Yanxiang (Journal of Applied Business and Economics, 2018)
This research examines the dynamics of the unemployment rate and jobless recoveries in The United States. We find that GDP, productivity, and inflation are positively related to employment recovery and real wage growth has a negative impact on employment recovery. A low inflation rate is a major factor associated with lengthened recoveries. The unemployment rate is significantly negatively related with productivity, real wage, and lagged GDP growth. Rising imports as a percentage of GDP put upward pressure on the unemployment rate. We find that unknown and unmeasurable factors associated with recessions are positively related to the unemployment rate.